Приватизация в Украине как социально-экономический процесс: объективные показатели и субъективные оценки - Резник, В. (Социология: теория, методы, маркетинг, 2006)
The article deals with the dynamics of objective indices and subjective estimations of
privatization in Ukraine. The author emphasizes the importance of a broader interpretation of the “privatization” notion that would allow to consider the above mentioned phenomenon as a social reinstitutionalization of private ownership, private enterprise,
and labor market. The abovementioned reinstitutionalization is to examine on the base
of structure ownership and employment indices in their dynamics. Such an analysis
allows to conclude that the market economy institutions are renewed as well as
parallelism and common tendencies in their forming exist. Moreover, the author
adduces opinions on privatization processes expressed by the Ukrainian citizens as
well as expert estimations of private ownership. All this gives grounds for assuming
that social delegitimization of the privatization process is not necessarily the case for
a similar delegitimization of the private ownership institution on the whole.